Cardiac Structure and Function Is Associated With Hemispatial Neglect Severity - Williams, Nicole L.; Suarez, Adrian; Negoita, Serban; Hillis, Argye E.; Gottesman, Rebecca F.; Johansen, Michelle C. (Frontiers in Neurology, 2021)
Background: Hemispatial neglect is a debilitating consequence of right hemispheric ischemic stroke (RIS), with evidence that patient-level factors influence neglect severity. Study objective: Determine if cardiac function is associated with presence and severity of neglect, independent of infarct size. Methods: Two hundred and eighteen non-demented, RIS with cerebral MRI and echocardiography who completed ≥1 of 4 tests evaluating neglect were included. Age- and sex- adjusted Z-scores defined neglect with severity categorized as no neglect, neglect on one or neglect on ≥2 tests. The dependent variable was presence of neglect (multivariable logistic regression), or neglect severity (multinomial logistic regression). The association with left ventricular (LV) structure/function (independent variable) was evaluated using separate nested adjustment models. Results: Patients were on average 61 yo (21–95), female (50%), black (53%), with an ejection fraction of 60% (IQR 20–75%). Fifty eight (27%) had neglect. Each 1 cm increase in LV systolic diameter was associated with a higher relative risk of having neglect on two tests compared to those with no neglect (RRR = 1.83, 95% CI 1.01–3.32), but not after adjusting for education and DWI volume (RRR = 1.68, 95% CI 0.89–3.19). Per 1 cm increase in left atrial (LA) diameter, the relative risk of having neglect on 2 tests vs. no neglect was over two times higher (95% CI 1.04–4.77), but lost significance in the final model (RRR = 1.73, 95% CI 0.76–3.94). Conclusions: We found an association between markers of diastolic dysfunction (enlarging LV, compensatory enlarging LA) and severity of neglect, suggesting that cardiac structure, and function affects not only lesion volume, but also the functional consequences of infarct volume.